Pengaruh Budaya Organisasi dan Iklim Organisasi Terhadap Loyalitas Kerja Pada Dinas Koperasi Perindustrian dan Perdagangan Kota Bima - Muhammad Al Fajrin; Jaenab (CV. Eureka Murakabi Abadi, 2023)
This study aims to determine the significant influence of organizational culture and organizational climate on employee loyalty at the Office of Cooperatives, Industry and Trade, Bima City. This type of research is associative with the research instrument being a questionnaire. The population in this study were 40 ASN employees and 20 temporary employees, so a total of 60 employees while the sample was 40 employees with ASN status using a purposive sampling technique. Data collection techniques in this study used observation, questionnaires, documentation and literature study. The analysis technique used in this research is validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient, determination coefficient, t test and f test processed using SPSS version 20. From the analysis results it can be concluded that there is an influence partially significant relationship between organizational culture on employee loyalty, there is a partial significant effect between organizational climate on employee loyalty, there is a simultaneous influence between organizational culture and organizational climate on employee loyalty.